Perlindungan Hukum Bagi Konsumen Atas Penggunaan Botol Berbahan Polikarbonat yang Tercemar Bisphenol- A Berdasarkan Undang-Undang Nomor 8 Tahun 1999 - I Made Anoraga Okky Dharmala; I Nyoman Gede Sugiartha; Luh Putu Suryani (Warmadewa Press, 2025)
Bisphenol-a is a chemical ingredient in polycarbonate plastics, which has shown negative effects on brain tissue. BPOM found the following compound in excess of 0.9 ppm per liter in polycarbonate gallon drinking water. Although the safe threshold is set at 0.6 parts per million (ppm) during 2021-2022 in 6 regions in Indonesia. The problems are: (1) How is the regulation of the use of drinking bottles made from polycarbonate? (2) How is legal protection for consumers for the use of polycarbonate bottles contaminated with bisphenol-a? This research uses normative legal research. According to the findings of this research, BPOM Regulation number 20 of 2019 concerning Food Packaging Supervision regulates the use of Bisphenol-a in drinking water containers. that the distribution threshold of bisphenol-a in food containers is no more than 0.6 bpj (600 microgram/kg) from polycarbonate packaging. The form of legal protection for consumers is the existence of food laws as a way to ensure panga safety. As well as by setting food packaging standardization. In relation to bisphenol-a, the government is obliged to protect the legal rights of consumers by regulating, fostering, and supervising polycarbonate drinking bottles.